Determinação do Shelf-Life de um novo processo de fabricação de sidra após diferentes tratamentos de conservação - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Cider is a drink obtained from the alcoholic fermentation of apple juice. Statistical data have shown a growing demand for the drink, mainly due to its low alcohol content and gluten-free content. However, the cider developed (INPI BR BR020130170348) focused on its refrigerated commercialization. In this sense, the present work aimed to reformulate the drink and evaluate different conservation treatments to ensure the quality and safety of this drink, making it possible to commercialize it at room temperature. The experimental cider was subjected to heat treatment conditions (60 and 80 oC for 15 min) and chemical treatment with potassium sorbate (0.03 mg L-1). These treatments were compared with the beverage stored at room temperature (± 20 oC) and refrigerated (7 to 10 oC). Beverages were evaluated at times zero, 30, 60 and 180 d of storage. Microbiological (yeasts, lactic acid bacteria, Salmonella spp., Escherichia coli and total coliforms) and physicochemical analyzes (density, pH, total and volatile acidity, alcohol content, total phenolics, phenolic profile, antioxidant activities and color) were performed. microbiological conditions, indicated good processing conditions and safety of the beverage, where a minimum count of E. coli and total coliforms (< 3 NMP mL-1) and absence of Salmonella spp. were obtained. In the samples submitted to heat treatments, the populations of fungi and yeasts were reduced by up to 93% right after the treatment and at the end of 180 d, about 3.0 CFU mL-1 remained for the cider pasteurized at 80 oC. As for lactic acid bacteria, pasteurization at 80 oC caused a further reduction. greater than the initial population, resulting in a decrease above 99%, which was maintained until the end of the monitoring and, therefore, the ciders remained microbiologically safe for 6 months at room temperature. physicochemical lysis, pasteurizations at 60 and 80 oC maintained the stability of the sugar and alcohol contents of the ciders during the 180 d of monitoring, keeping these parameters within the requirements of current legislation. Despite oscillations, the ciders showed compliance with current legislation regarding total acidity (50 to 130 mEq L-1) and volatile acidity (< 30 mEq L-1), with the exception of ambient control. The cider pasteurization at 80 oC caused the greatest loss of total phenolic content among the pasteurized samples, being 8.6%. Pasteurized ciders showed gradual decreases in their antioxidant activities by FRAP, DPPH and ABTS of up to 32.7; 45.5 and 48.6%, respectively. There were also marked color changes during storage, where pasteurized ciders showed significant browning. The addition of 0.03 mg L-1 of potassium sorbate was not efficient to control/inhibit microbial growth. Although pasteurizations at 80 and 60 oC were able to provide microbiological safety for six months due to the reduction of microbial load, with the 80 oC being more efficient, the treatments significantly affected the antioxidant activities and the color of the drinks, guaranteeing promising results for up to two months. storage, and the treatment at 60 oC showed better results. Considering sensory issues, such as the taste of the drink, the most suitable method for the conservation of cider was pasteurization at 60 oC 15 min-1 and the commercial shelf life of ciders was better established at 60 d.
Keywords: Frisante de maçã; Pasteurização; Conservantes químicos; Qualidade microbiológica; Composição química; Apple sparkling wine; Pasteurization; Chemical preservatives; Microbiological quality; Chemical composition; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS